46.6k views
2 votes
X-3y=-14
x-y=-2
substution method

User Bpossolo
by
4.9k points

1 Answer

2 votes

Answer:

(4, 6 )

Explanation:

x - 3y = - 14 ( add 3y to both sides )

x = - 14 + 3y → (1)

x - y = - 2 → (2)

Substitute x = - 14 + 3y into (2)

- 14 + 3y - y = - 2

- 14 + 2y = - 2 ( add 14 to both sides )

2y = 12 ( divide both sides by 2 )

y = 6

Substitute y = 6 into (1)

x = - 14 + 3(6) = - 14 + 18 = 4

solution is (4, 6 )

User Tdammers
by
5.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.